Physiological Responses to Abiotic and Biotic Stress in Forest Trees - Polle, Andrea; Rennenberg, Heinz (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
As sessile organisms, plants have to cope with a multitude of natural and anthropogenic forms of stress in their environment. Due to their longevity, this is of particular significance for trees. As a consequence, trees develop an orchestra of resilience and resistance mechanisms to biotic and abiotic stresses in order to support their growth and development in a constantly changing atmospheric and pedospheric environment. The objective of this Special Issue of Forests is to summarize state-of-art knowledge and report the current progress on the processes that determine the resilience and resistance of trees from different zonobiomes as well as all forms of biotic and abiotic stress from the molecular to the whole tree level.